Conectadas: uma análise de práticas de ajuda mútua feminina na era das mídias digitais - Facioli, Lara Roberta Rodrigues (Universidade Federal de São Carlos, 2013)
The present work focus on investigating processes of subjectivity in contemporary self-help speeches aiming the female audience, which when penetrating the network through a specific form of using digital media, they become practical mutual help. To achieve this goal, I established three main lines of research, which I will discuss through a ethnographic method: the website Bolsa de Mulher, with its discussion forums, advertisements and products sales and the group created by the users on Facebook, the lines among users within that platform, their life stories and experiences both with the internet and the self-help speech; finally, some books of this genre, most cited by my collaborators and some of the best selling in recent years, in Brazil. I discuss a theoretical framework that examines issues of subjectivity through the use of digital media as well as one that addresses a perspective of intersectionality of class differences, gender, sexuality, race, religion, all markers crossing such use. Last but not least, I problematize and bring into discussion the sociological debate around the so-called New Class C, public that composes this research and has specific characteristics regarding the use of digital media and the dynamics of mutual help, in Brazil.
Keywords: Gênero; Diferença entre gêneros; Relações de ajuda; Mídia digital; Processos de subjetivação; Marcadores da diferença; Classe C; Subjectivation processes; Digital media; Markers of difference; Class C; CIENCIAS HUMANAS::SOCIOLOGIA